Biodiversity, feeding habits and reproductive strategies of benthic macrofauna in a protected area of the northern Adriatic Sea: a three-year study - NASI, F.; AURIEMMA, R.; BONSDORFF, E.; CIBIC, T.; ALEFFI, I. F.; BETTOSO, N.; NEGRO, P. DEL (Mediterranean Marine Science, 2017)
The macrozoobenthic community at a sublittoral station located in the Marine Protected Area of Miramare, Gulf of Trieste (Italy) was investigated monthly from June 2002 to July 2005. Community variables were studied and related to food sources (particulate, total and biopolymeric carbon contents, benthic microalgae and meiofauna). In addition, the macrofaunal response to a heatwave that occurred in summer 2003 in the area was also explored. Univariate and multivariate analyses highlighted that the macrozoobenthic community structure shifted towards the end of the study. Diversity remained fairly stable throughout the study, despite the high turnover values. From a dominance of short-lived invertebrates related to irregular fresh organic matter inputs, the community shifted toward long-lived taxa, principally related to an increase of biopolymeric C and microalgal biomass. Semelparous invertebrates seem to be less resistant to high temperatures compared to iteroparous ones. The latter proved to be capable competitors since they prevailed over the semelparous species towards the end of the study. The community exhibited a certain degree of resistance to high temperature, due to the adaptation of the macrofaunal invertebrates to this particular stress, induced by the wide natural fluctuations in temperature that occur on a seasonal basis in the Gulf of Trieste. This study highlights the importance of long datasets to assess the state and ecological processes of the macrofaunal communities.